The role of iron homeostasis and iron-mediated ROS in cancer - Ying, Jia-Fu (Am J Cancer Res, 2021)
As an important trace element, iron plays an essential role in many biology processes like cell proliferation, metabolism, and mitochondrial function. However, the disruption of iron homeostasis tends to cells death and human diseases due to it servers as mediator to promote the production of reactive oxygen species (ROS). In this review, first we introduced the mechanism of complex iron-mediated ROS involved in apoptosis, necroptosis, ferroptosis and pyroptosis. Next, we discussed the controversial role of excess iron and iron deficiency in tumor. Finally, we discussed the anti-cancer effects of iron on both sides, and novel iron-related strategies. This review outlined the mechanisms and regulation of iron homeostasis and iron-mediated ROS in tumors, and discussed the iron-related treatments.